Immediate Cementless Hemiarthroplasty for Severe Destructive Glenohumeral Tuberculous Arthritis - Suriya Luenam; Arkaphat Kosiyatrakul (Case Reports in Orthopedics)
The glenohumeral joint tuberculosis (TB) is rare as compared with other joints. Plaster immobilization, arthrodesis, and resection arthroplasty have been proposed as the additional treatments with anti-TB medications in severe destructive arthritis. To our knowledge, however, the surgical treatment with shoulder arthroplasty has never been reported. We present two cases of active TB with unsalvageable glenohumeral joint. The cementless hemishoulder arthroplasties were performed immediately following the radical debridement. Anti-TB medications were given for 12 months after the surgery. Postoperatively, the patients were satisfied with the rapid symptomatic relief and significant functional recovery. With the follow-up period of 5 years, the operative results were still satisfactory and the reactivation of the infection was not detected.